Novel aqueous micellar two-phase systems with ionic liquids - Vicente, Filipa Alexandra André (2018)
This work addresses the design of novel aqueous micellar two-phase systems (AMTPS) using ionic liquids (ILs) as a new class of co-surfactants for extractive processes and the assessment of their potential of application to the extraction of diverse (bio)molecules. Firstly, the coexistence curves of AMTPS based on the surfactant Triton X-114 and distinct ILs composed of imidazolium, phosphonium and quaternary ammonium structures were determined. These allowed the investigation of the impact of IL absence/presence, concentration and structural features on the behavior of the coexistence curves. The designed AMTPS were then used to carry out partition studies involving two model (bio)molecules, the protein Cytochrome c and the dye Rhodamine 6G. It was shown that the presence of ILs as co-surfactants is able to enhance not only the partition coefficients, but also the selectivity parameters of the process. These AMTPS were also applied to the extraction of the natural colorant curcumin from its vegetal extract with complete recovery into the micelle-rich phase however, there are interactions, yet unknown, affecting curcumin extraction. Finally, the new AMTPS were proposed as suitable techniques to be used in the domain of analytical chemistry. Hence, they were used in the extraction of tenofovir disoproxil fumarate, an antiretroviral, in order to facilitate its detection. After optimizing several operational parameters, it was possible to attain extraction efficiencies up to 100%. As the current techniques may present low efficiencies and require the use of organic solvents, AMTPS are envisaged as more sustainable approaches.